The Future Prospect of Rattan as Food Resources in Central Kalimantan - Kalima, Titi; Susilo, Adi (Proceeding International Conference on Global Resource Conservation, 2015)
Rattan plays an important role as food resources in the culture of the Dayak communities living near forest areas. Shoot of rattan is cooked by the Dayaks to make a dish "sayur umbut rotan". This stir-fried rattan shoot cuisine is always served in the event of Dayak traditional ceremonies. The aim of this study was to identify and inventory of rattan species that uses in the Dayak food. The study was carried out at the villages of Mantangai Hulu, Kalumpang, Katimpun, Sei Ahaz and Katunjung, in the Kapuas District, Central Kalimantan Province. The method used ware interviewing local community, making field observation and collecting voucher specimen of rattan for identification in the Herbarium of Center for Conservation and Rehabilitation Research and Development. Result of the study was revealed that six species of rattan were used in the Dayak foods which are Calamus caesius Blume, C. trachycoleus Beccari, C. ornatus Blume ex Schult. & Schult.), Daemonorops crinita Blume, D. fissa Blume, and Plectocomiopsis geminiflora (Griff.) Beccari. It is recommended that these six species of rattan should be cultivated in their garden to lessen disturbance to the natural population.Â Key words: Dayak; local communities; rattan; traditional food